Nanotechnology and drug delivery - Arias, Jose L. (Boca Raton : Taylor & Francis, 2014)
'Pharmacotherapy is often limited by the inefficient activity and severe toxicity of drug molecules. Nanotechnology offers a revolutionary and definitive approach for the efficient delivery of drug molecules to non-healthy tissues and cells. This first volume of a series of two volumes analyzes the basics in the development of drug-loaded nanoplatforms, the so-called nanomedicines. Special attention is given to physicochemical engineering, pharmacokinetics, biocompatibility and biodegradability, representative nanoplatforms (based on lipids, polymers, cyclodextrins, metals, carbon, silica, iron oxides, etc.), and advanced nano-engineering strategies for passive, ligand-mediated, and/or stimuli-sensitive drug delivery and release'--Provided by publisher.
Volume 1. Nanoplatforms in Drug Delivery.
Includes bibliographical references and index.
Keywords: Drug delivery systems; Nanoparticles; Drug Design; Nanotechnology -- methods; Drug delivery systems; Nanomedicine